Cortical Oscillations and Connectivity During Postoperative Recovery. Issue 1 (January 2021) - Zierau, Mackenzie; Li, Duan; Lapointe, Andrew P.; Ip, Ka I.; McKinney, Amy M.; Thompson, Aleda; Puglia, Michael P.; Vlisides, Phillip E.
Abstract : Background: The objective of this study was to test whether postoperative electroencephalographic (EEG) biomarkers, parietal alpha power and frontal-parietal connectivity, were associated with measures of clinical recovery in adult surgical patients. Methods: This is a secondary analysis of a prospective cohort study that analyzed intraoperative connectivity patterns in adult surgical patients (N=53). Wireless, whole-scalp EEG data were collected in the postanesthesia care unit and assessed for relevance to clinical and neurocognitive recovery. Parietal alpha power and frontal-parietal connectivity (estimated by weighted phase lag index) were tested for associations with postanesthesia care unit discharge readiness and University of Michigan Sedation Scale scores upon postoperative admission. Bivariable correlation and regression models were constructed to test for unadjusted associations, then multivariable regression models were constructed to adjust for confounding. Results: Postoperative EEG patterns were characterized by a predominance of alpha parietal power and frontal-parietal connectivity. Neither relative parietal alpha power (% alpha, −0.25; 95% confidence interval [CI], −1.41 to 0.90; P =0.657) nor alpha frontal-parietal connectivity (weighted phase lag index, −82; 95% CI, −237 to 73; P =0.287) were associated with time until postanesthesia discharge criteria were met. Furthermore, neither alpha power (−0.03; 95% CI, −0.07 to 0.01; P =0.206) nor alpha frontal-parietal connectivity (−4.2; 95% CI, −11 to 2.6; P =0.226) were associated with sedation scores upon initial assessment. Conclusions: In a pragmatic study investigating clinically relevant endpoints of postoperative recovery, we found no correlation with surrogate measures of brain neurodynamics. These data contribute to the overall impetus of developing anesthetic-invariant and generalizable markers of brain recovery. Abstract : Supplemental Digital Content is available in the text.